Sinapic acid alleviates inflammatory bowel disease (IBD) through localization of tight junction proteins by direct binding to TAK1 and improves intestinal microbiota - Jang, Sehyeon; Kim, San; So, Bo Ram; Kim, Younghoon; Kim, Chang-Kil; Lee, Jeong Jae; Jung, Sung Keun (Frontiers in Pharmacology, 2023)
Introduction: Although sinapic acid is found in various edible plants and has been shown to have anti-inflammatory properties including colitis, its underlying mechanism and effects on the composition of the gut microbiota are largely unknown. We aimed to identify an early response kinase that regulates the localization of tight junction proteins, act at the onset of the inflammatory response, and is regulated by sinapic acid. Additionally, we analyzed the effects of sinapic acid on the homeostasis of the intestinal microbiome. Methods: We examined the aberrant alterations of early response genes such as nuclear factor-kappa B (NF-κB) and activating transcription factor (ATF)-2 within 2 h of sinapic acid treatment in fully differentiated Caco-2 cells with or without lipopolysaccharide and tumor necrosis factor (TNF)-α stimulation. To confirm the effect of sinapic acid on stimulus-induced delocalization of tight junction proteins, including zonula occludens (ZO)-1, occludin, and claudin-2, all tight junction proteins were investigated by analyzing a fraction of membrane and cytosol proteins extracted from Caco-2 cells and mice intestines. Colitis was induced in C57BL/6 mice using 2% dextran sulfate sodium and sinapic acid (2 or 10 mg/kg/day) was administrated for 15 days. Furthermore, the nutraceutical and pharmaceutical activities of sinapic acid for treating inflammatory bowel disease (IBD) evaluated. Results: We confirmed that sinapic acid significantly suppressed the stimulus-induced delocalization of tight junction proteins from the intestinal cell membrane and abnormal intestinal permeability as well as the expression of inflammatory cytokines such as interleukin (IL)-1β and TNF-α in vitro and in vivo. Sinapic acid was found to bind directly to transforming growth factor beta-activated kinase 1 (TAK1) and inhibit the stimulus-induced activation of NF-κB as well as MAPK/ATF-2 pathways, which in turn regulated the expression of mitogen-activated protein kinase (MLCK). Dietary sinapic acid also alleviated the imbalanced of gut microbiota and symptoms of IBD, evidenced by improvements in the length and morphology of the intestine in mice with colitis. Discussion: These findings indicate that sinapic acid may be an effective nutraceutical and pharmaceutical agent for IBD treatment as it targets TAK1 and inhibits subsequent NF-κB and ATF-2 signaling.